Narrowband ultraviolet B phototherapy in children with moderate‐to‐severe eczema: a comparative cohort study. (1st January 2014) - Darné, S.; Leech, S.N.; Taylor, A.E.M.
Summary: Background: There is only retrospective evidence for the efficacy of narrowband ultraviolet B (NB‐UVB) in children with eczema. Objectives: To measure the difference in means for objective scores [Six Area Six Sign Atopic Dermatitis score (SASSAD), percentage surface area] and quality‐of‐life scores, between patients treated with NB‐UVB and unexposed cohorts at the end of treatment, and 3 and 6 months post‐treatment. Methods: Twenty‐nine children aged 3–16 years for whom NB‐UVB was indicated, were scored prospectively using SASSAD and percentage surface area involvement at baseline, at 12 weeks (end of treatment) and 3 and 6 months post‐NB‐UVB. Their scores were compared with those of unexposed children ( n = 26) for whom NB‐UVB phototherapy was indicated and offered, but who chose not to undertake treatment. Results: There was a 61% reduction in mean SASSAD score in the NB‐UVB cohort compared with an increase of 6% in the unexposed cohort. Mean SASSAD score for the NB‐UVB cohort at the end of treatment was 11·6 vs. 24·8 for the unexposed; difference in means −13·2 [95% confidence interval (CI) −18·7 to −7·7, P < 0·0001]. Mean surface area involvement at the end of treatment was 11% for the NB‐UVB cohort vs. 36% for the unexposed cohort; difference in means −25% (95% CI −34% to −16%, P < 0·0001). Subjective and quality‐of‐life scores showed significant difference between cohorts at the end of treatment ( P < 0·05). Objective scores remained significantly lower than in the unexposed cohort 3 and 6 months after treatment. Conclusion: NB‐UVB is clinically effective and improves quality of life in children with moderate‐to‐severe eczema. The effect is maintained for 6 months after treatment.